Organization of American States and the Commonwealth Caribbean : perspectives on security, crisis and reform - Bryan, Anthony T. ed. (Institute of International Relations St AugustineTT, 1986)
Analyzes the historical role of the OAS in the interamerican system. Discusses the participation of the Commonwealth Caribbean States in the OAS and focuses on issues such as hemispheric security and the peaceful settlement of disputes. Discusses the ammended OAS charter, its juridical validity and the political considerations that motivated its authors and supporters. Examines some of the legal issues raised by the membership of small English-speaking states in the OAS.